The Influence of Hollywood Squares Learning Strategy on Science Learning Motivation for Fifth Grade Student of Elementary School - Salwa Sholihatunnisa; Safrul Safrul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study was intended to determine whether or not there is an effect of giving the Hollywood Squares on the motivation to learn science. The method in this research is an experiment using Quasi Experimental and Posttest-Only Control Design. The fifth grade students of Jatirasa II State Elementary School as the population in this study were 53 students. The sample used by the researcher used a census sampling or the total sample from class VA consisted of 26 students and class VB consisted of 27 students. The instrument in this study used a questionnaire totaling 23 statements that were tested valid and reliable. The researcher used the Shapiro Wilk formula as a normality test, then calculated the  Levene homogeneity formula independent t-test as a hypothesis test. The data obtained by the control group and the experimental group resulted in a t-test on tcount> ttable = 2,236 > 1,681 with a significance of 5%, so that the conclusion was Ho rejected, which means that there is an influence of the Hollywood Squares on the motivation to learn science in class V Jatirasa II State Elementary School .